Nevoid Basal-Cell Carcinoma (Gorlin) Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
A unique case of a 15-year-old girl with nevoid basal-cell carcinoma (NBCCS), who presented with uncontrolled temporal lobe epilepsy due to neuronal heterotopia, is reported from the Royal Melbourne Hospital, Australia.